Effect of tylosin on ruminal Fusobacterium necrophorum population and fermentation products in cattle fed a high-grain diet - N. Wallace; Y. Sun; Kenneth E. Kemp; J.C. Parrott; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1998)
Tylosin feeding prevented the increase in Fusobacterium necrophorum population normally associated with the feeding of a high-grain diet. Also, tylosin appeared to moderate the ruminal fermentation during initial adaptation to a high-grain diet.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen& #x27; s Day; 1998; Beef; Tylosin; Fusobacterium necrophorum; High-grain diet